Let Zia's age be = x years
Raj is three years older than Zia, so Raj's age = x+3 years
As the sum of the squares of their ages is 369, so
![x^(2)+(x+3)^(2)=369](https://img.qammunity.org/2019/formulas/mathematics/middle-school/nwmkkrfbgk51rq8pqh4ee2yik0a5ulhbv9.png)
![x^(2)+x^(2)+6x+9=369](https://img.qammunity.org/2019/formulas/mathematics/middle-school/tngk47m5z0bz5z5v5cb714vj66hmgri577.png)
![2x^(2)+6x+9=369](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qi447rh0vmcf9ktww3mj7y3gkbw4wp6rg2.png)
![2x^(2)+6x-360=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hwf78b589kns01t8xyp71i3y3tduz7a31e.png)
Factoring 2 out we have,
![x^(2)+3x-180=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/3g5fv0dcwjgqckm074cd8t8r77uco5v0bt.png)
Now solving this equation,
![x^(2)+15x-12x-180=0](https://img.qammunity.org/2019/formulas/mathematics/middle-school/f96bb3gm4dil1bqtpqb9r8h6laq7y1rtqz.png)
![x(x+15)-12(x+15)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6xpgqjt83c1w1t4x2h5tiw38aqm4i9ymfo.png)
![(x+15)(x-12)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cl7n3te01m2rux5xvncftgvuvv48api711.png)
x=-15 and x=12
Neglect the negative value as x cannot be negative
So x=12
Hence, Zia's age is 12 years and
Raj's age is 12+3 = 15 years